Efektivitas Terapi Musik Alam terhadap Tingkat Kecemasan pada Pasien Hemodialisis - Wiyanna Mathofani Siregar; Dudut Tanjung; Elmeida Effendy (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to identify and evaluate the effect of natural music therapy intervention on hemodialysis patients. This research uses quantitative methods with a quasi-experimental non-equivalent control group pretest-posttest design. Respondents in this study were 96 hemodialysis patients. Data were collected using a State Anxiety Inventory (SAI) questionnaire comprising 20 statement items. Data were analyzed using nonparametric tests (Wilcoxon Signed Rank Test and Mann Whitney U Test). The results showed a difference between the mean value of anxiety in the intervention group and the control group, namely 37.90 in the intervention group and 42.33 in the control group, with a p-value of 0.048. In conclusion, natural music therapy is recommended as an alternative to reduce the level of anxiety in hemodialysis patients to improve the patient's quality of life. Keywords: Hemodialysis, Anxiety, Natural Music Therapy